Commensurate Assembly of C60 on Black Phosphorus for Mixed‐Dimensional van der Waals Transistors. Issue 10 (12th January 2022) - Yun, Tae Keun; Lee, Yangjin; Kim, Min Je; Park, Jeongwoo; Kang, Donghee; Kim, Seongchan; Choi, Young Jin; Yi, Yeonjin; Shong, Bonggeun; Cho, Jeong Ho; Kim, Kwanpyo
Abstract: 2D crystals can serve as templates for the realization of new van der Waals (vdW) heterostructures via controlled assembly of low‐dimensional functional components. Among available 2D crystals, black phosphorus (BP) is unique due to its puckered atomic surface topography, which may lead to strong epitaxial phenomena through guided vdW assembly. Here, it is demonstrated that a BP template can induce highly oriented assembly of C60 molecular crystals. Transmission electron microscopy and theoretical analysis of the C60 /BP vdW heterostructure clearly confirm that the BP template results in oriented C60 assembly with higher‐order commensurism. Lateral and vertical devices with C60 /BP junctions are fabricated via a lithography‐free clean process, which allows one to investigate the ideal electrical properties of pristine C60 /BP junctions. Effective tuning of the C60 /BP junction barrier from 0.2 to 0.5 eV and maximum on‐current density higher than 10 4  mA cm −2 are achieved with graphite/C60 /BP vertical vdW transistors. Due to the formation of high‐quality C60 film and the semitransparent graphite top‐electrode, the vertical transistors show high photoresponsivities up to ≈100 A W −1 as well as a fast response time under visible light illumination. Abstract : Oriented assembly of C60 molecular layers on the puckered substrate of black phosphorus is achieved via higher‐order commensurism. Mixed‐dimensional van der Waals transistors incorporating ordered C60 films on black phosphorus exhibit superior optoelectronic properties including largely tunable junction barriers and high photoresponsitivies.